Memoirs of a Cavalier : A Military Journal of the Wars in Germany, and the Wars in England. From the Year 1632 to the Year 1648. - Defoe, Daniel, 1661?-1731 (Salt Lake City, UT : Project Gutenberg, 2004)
"Memoirs of a Cavalier" by Daniel Defoe is a work of historical fiction published in 1720. The story follows an English gentleman-soldier through two devastating conflicts: the Thirty Years' War in Germany, where he serves under the legendary Swedish King Gustavus Adolphus, and the English Civil War, where he fights for King Charles the First. Through one man's military journal spanning 1632 to 1648, Defoe chronicles the grand sweep of European warfare and political upheaval during a tumultuous era. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Memoirs_of_a_Cavalier
Release date is 2004-05-01
Produced by Audrey Longhurst, Audrey Longhurst, Leah Moser and the Online Distributed Proofreading Team
Keywords: Historical fiction; War stories; Thirty Years' War, 1618-1648 -- Fiction; Soldiers -- Fiction; Great Britain -- History -- Civil War, 1642-1649 -- Fiction; Royalists -- Fiction; Great Britain -- History, Military -- 1603-1714 -- Fiction